2010
DOI: 10.3102/0002831209351563
|View full text |Cite
|
Sign up to set email alerts
|

Black Male Teachers as Role Models: Resisting the Homogenizing Impulse of Gender and Racial Affiliation

Abstract: This article reports on research with one Black male elementary school teacher in Toronto and draws on feminist, queer, and antiracist analytic perspectives to raise important questions about the discourse of teachers as role models. The voice of this teacher is used to challenge discourses about role modeling in their capacity to address adequately the limits imposed by both cultural and structural problems experienced by minority boys in urban school communities. Important questions about the role of teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Rather than defined as a power relationship, gender and other equality matters (such as race, particularly in the US context) becomes constructed as a commodity or as a form of human capital which is instrumentalised by policy-makers and school managers, as is the case when they recruit male teachers to improve students' performance. Often, there is limited consideration of how this commodification of equality matters affect teachers (Rezai-Rashti and Martino, 2010;Brown, 2012). Meanwhile, in England, other gender issues, such as women teachers' under-representation in leadership and management positions, tend to be absent from and simultaneously compounded by policy discourses (Moreau et al, 2008;Cushman, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than defined as a power relationship, gender and other equality matters (such as race, particularly in the US context) becomes constructed as a commodity or as a form of human capital which is instrumentalised by policy-makers and school managers, as is the case when they recruit male teachers to improve students' performance. Often, there is limited consideration of how this commodification of equality matters affect teachers (Rezai-Rashti and Martino, 2010;Brown, 2012). Meanwhile, in England, other gender issues, such as women teachers' under-representation in leadership and management positions, tend to be absent from and simultaneously compounded by policy discourses (Moreau et al, 2008;Cushman, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is now nuanced data that speak to the value of a diverse educational workforce. For example, student exposure to ethnically and racially diverse educators has positive academic outcomes (Gershenson, Hart, Hyman, Lindsay, & Papageorge, 2018); increases attendance rates of SOCs (Achinstein, Ogawa, Sexton, & Freitas, 2010); enables the advancement of SOCs in mathematics (Eddy & Easton-Brooks, 2011); yields positive effects in reading when students are paired with race-congruent teachers (Egalite, Kisida, & Winters, 2015); increases referrals to gifted programs for Black and Latinx students (Grissom & Redding, 2015); and leads to decreased discipline gaps between Black and White students (Monroe, 2009;Rezai-Rashti & Martino, 2010).…”
Section: Consequences Of the Brown Decision On Educator Diversitymentioning
confidence: 99%
“…Male teachers of color are underrepresented in nearly every PK-12 subject area (Singh 2018;Vilson 2015;Waite, Mentor, and Bristol 2018). While it is possible that males of color are less interested in entering the teaching profession when compared to other demographic groups, research has suggested that the underrepresentation of males of color in the teacher workforce is a reflection of ethnoracial and gendered messages about teaching and learning that male students of color encounter in schools (Fergus 2009;Howard 2008); inadequate recruitment and retention efforts in teacher education programs (Woodson and Pabon 2016); and poor professional support and limited mentoring for this population (Bristol and Goings 2019;Rezai-Rashti and Martino 2010). This special issue provides an in-depth analysis of how male teachers of color are positioned, socialized, and supported in diverse contexts.…”
Section: Introductionmentioning
confidence: 99%